If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 + 6y = y Solving 55 + 6y = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 55 + 6y + -1y = y + -1y Combine like terms: 6y + -1y = 5y 55 + 5y = y + -1y Combine like terms: y + -1y = 0 55 + 5y = 0 Add '-55' to each side of the equation. 55 + -55 + 5y = 0 + -55 Combine like terms: 55 + -55 = 0 0 + 5y = 0 + -55 5y = 0 + -55 Combine like terms: 0 + -55 = -55 5y = -55 Divide each side by '5'. y = -11 Simplifying y = -11
| 35+2a=7a | | 2v^2-8=0 | | 28+9n=2n | | 5g+2(-6+5g)=1-g | | 24=18+2g | | 32-5m=52 | | 4-4h=12 | | 21+3y=0 | | 8x+5=19+x | | 55-11m=0 | | =(2m^2t^2+18mt-9m^2-12t^2)(-5m^2+8t^2) | | 12d-84=0 | | 3(x-5)=2(x+5) | | 4m-16=-36 | | -(n-1)=-2(n+3) | | 3+4d=39 | | 15x=255 | | 8q-8=72 | | =(5x+9y+8z)(-12x+10y-15z) | | 8m+6=54 | | 26-(4x-11)=-5(x+7) | | 15+9-3= | | 3(n-1)=2n+8 | | 5y-8=32 | | 15t+9q-3= | | 9+8q=14+7q | | 3d+4=2+3d-5 | | 7(d-2)=42 | | 14x+6=5x-3 | | x+11=2(x-1) | | 72-2x=7x+19 | | -7(15-h)=56 |